Lymphomatoid Granulomatosis in a Patient with Chronic Lymphocytic Leukemia and Rapidly Progressing Peribronchovascular Pulmonary Infiltrates. (21st January 2019) - Rezvani, Shahab; Tominna, Marie; Al-Katib, Sayf; Smith, Marc D.; Cousineau, Craig; Al-Katib, Ayad
Abstract : Lymphomatoid granulomatosis (LG) is an EBV-associated angiodestructive lymphoproliferative disease with multiorgan involvement that predominantly affects the lungs. We present a case of a 72-year-old man with a history of chronic lymphocytic leukemia who presented with upper respiratory symptoms and multiple erythematous skin papules. Chest CT showed ill-defined, irregular solid pulmonary nodules with peripheral ground-glass opacities in a peribronchovascular distribution. The differential for this pattern of lung disease is vast which includes but is not limited to infection, vasculitis, sarcoidosis, lymphoma, and Kaposi sarcoma. Subsequent PET/CT showed rapid progression of lung opacities and marked FDG uptake of pulmonary opacities and skin nodules, which raised the question of Richter syndrome. Wedge biopsy under video-assisted thoracoscopic surgery was performed. Pathology showed an extensive lymphoid infiltrate involving lymphatic and bronchovascular bundles and consisting of a mixture of large lymphocytes and inflammatory cells. Special stains showed that the large lymphocytes expressed B-cell markers and EBV virus. Overall, the findings were consistent with LG.